Gas-Forming Pyogenic Liver Abscess with Septic Shock - Muhammad S. Khan; Muhammad K. Ishaq; Kellie R. Jones (Case Reports in Critical Care)
The pyogenic liver abscess caused by Clostridium perfringens (C. perfringens) is a rare but rapidly fatal infection. The main virulence factor of this pathogen is its α-toxin (lecithinase), which decomposes the phospholipid in cell membranes leading to cell lysis. Once the bacteria are in blood stream, massive intravascular hemolysis occurs. This can present as anemia on admission with evidence of hemolysis as indicated by low serum haptoglobin, high serum lactate dehydrogenase (LDH), elevated indirect bilirubin, and spherocytosis. The clinical course of C. perfringens septicemia is marked by rapidly deteriorating course with a mortality rate ranging from 70 to 100%. The very rapid clinical course makes it difficult to diagnose on time, and most cases are diagnosed at autopsy. Therefore it is important to consider C. perfringens infection in any severely ill patient with fever and evidence of hemolysis. We present a case of seventy-seven-year-old male with septic shock secondary to pyogenic liver abscess with a brief review of existing literature on C. perfringens.